IABSE Symposium, Vancouver 2017: Engineering the Future 2017
DOI: 10.2749/222137817822208528
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of slab-column concrete connections at elevated temperatures

Abstract: <p>Flat slab-column concrete frames are an economical type of concrete building. The main advantages of this type of frame structure are that they are easy to construct, relatively cheap to build and offer flexible column arrangement. However, they are susceptible to a type of failure known as “punching shear”, where columns “punch” through slabs. This is a particularly dangerous type of failure as it occurs suddenly. Punching shear occurring at high temperatures, such as in fire, is an obvious concern. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Where; ε is the total strain, ε is the mechanical strain resulting from the mechanical load, ε is the thermal strain due to the material expansion, ε is the load-induced thermal strain resulting from the concrete shrinking under a high level of mechanical loading and ε is the creep strain that develops in the material due to external loading over time. The modelling approach adopted by Al Hamd et al [41,42] gives good results showing a close comparison with experimental data for ambient and elevated temperatures validation (further details on the model can be found in [41,42]). The same approach was applied to the models with shearhead reinforcement described in the previous section to examine the effect of the shearhead presence in the connection.…”
Section: The Effect Of Fire On the Proposed Shearhead Systemmentioning
confidence: 86%
“…Where; ε is the total strain, ε is the mechanical strain resulting from the mechanical load, ε is the thermal strain due to the material expansion, ε is the load-induced thermal strain resulting from the concrete shrinking under a high level of mechanical loading and ε is the creep strain that develops in the material due to external loading over time. The modelling approach adopted by Al Hamd et al [41,42] gives good results showing a close comparison with experimental data for ambient and elevated temperatures validation (further details on the model can be found in [41,42]). The same approach was applied to the models with shearhead reinforcement described in the previous section to examine the effect of the shearhead presence in the connection.…”
Section: The Effect Of Fire On the Proposed Shearhead Systemmentioning
confidence: 86%
“…al. [9,10] which demonstrated more realistic results in capturing the structural behaviour of the slab-column connection. Although some limited experimental work has been conducted to examine the effect of loading ratio, no numerical study incorporating accurate capture of LITS has been carried out to date in this particular application.…”
Section: Background and Motivationmentioning
confidence: 98%
“…Al-Hamd et al [9,10] put forward an explanation for the unexpected behaviour reported in the experimental tests conducted by [5][6][7][8] for the slab-column connections. The main reason for this behaviour is found to be the activation of one of the strain components (LITS) of the heated concrete generated under combined heating and high levels of loading conditions.…”
Section: Effect Of Heating On the Strain Components Of Concretementioning
confidence: 99%
See 2 more Smart Citations